Scientific Validity of Approaches to Solving a Number of Agricultural Problems in Azerbaijan - Aliyev, RAE. Z. H.; Jafarov, A. B. (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Annotation: The Republic of Azerbaijan, which translates into a physically-geographical area, a way to the eastern part of the Caucasus, where the Big and Small Caucasus, Tallinn Region, Kurinskaya oblast and Nakhichevan. The Republic is 86.6 this. Per km2 or 40% of the landfill make up the oil, 60% of the landfill, and snow. He small Caucasus and its lowlands, the complex geographical location of Azerbaijan’s historic lands, have been inhabited for thousands of years and have been used extensively in agriculture and livestock. The complexity of the natural conditions here and the ineffective activities of people have led to increased anthropogenic pressures and exogenous processes, which have led to catastrophic erosion processes that have developed and developed. The results of the soil-erosion study conducted in the occupied territories of the region (2004-2012) show that all types of erosion, including surface, linear, silt, grass, as a result of the complex geological and geomorphological situation of the Karabakh region and the combined impact of anthropogenic pressure. Wind and military erosion have developed in a wide range and are measured by the following average statistics. Goranboy-40.9%; Tartar - 45.0%; Aghdam - 31.3%; Barda - 23.2%, Yevlakh - 26.4%; Kelbajar - 52.4%; Beylagan - 19.8%; Aghjabadi - 15.7%; Fizuli - 45.7%; Gabriel - 63.3%; Zinc - 57.7%; Qubatly - 44.0%; Lachin - 48.0%; Serum-20.9%; Upper Karabakh - 37.0%, which means that 884,000 ha of agricultural land is in danger of being out of crop rotation.